Lateral ankle stabilization with a polyester fiber construct implant as a revision for failed primary lateral ligament reconstruction - Hermida Galindo, Luis Felipe; Hermida Ochoa, Elias; Torres Gomez, Armando (Journal of the Foot & Ankle, 2020)
Objective: The aim of this study is to demonstrate an original technique in which a stable construct is made by fibular and calcaneal bone tunnels producing a figure of 8 with a Polyester implant as revision for failed primary ligament reconstruction. Methods: This is a retrospective study of 19 patients with persistent lateral ankle instability diagnosis after a primary ligament repair treated between 2011 and 2019. The surgical technique is described in detail in which stabilization of the lateral ankle is performed. 11 men and 8 women with a mean age of 30.94 years (15-53). Follow up was 29.05 months (6-109). Pre and postoperative AOFAS ankle score were used as well as an AVS and a satisfaction questionnaire. Results: There was a significant improvement in AOFAS score, 76.31 to 91.47 (<0.001). All the patients except one, stated to have a stable ankle and be Very satisfied (16) or satisfied (2) with the procedure. No infection was presented in any patient. Conclusion: This technique is a reliable alternative in patients in which primary ankle ligaments have failed and no autograft or allograft are wanted to be used. Level of Evidence V; Therapeutic Study; Expert Opinion.